Host-parasites relationship for Lake Victoria Clariid fishes and their parasite fauna - Mwita, C. J. (Tanzania Journal of Science, 2021)
Host-parasite co-evolutionary relationships for the clariid fish species of the Lake Victoria basin and their parasite fauna was inferred by cytochrome b gene and the 18S rDNA using ‘a strict coevolutionary’ constrained tree method, the results of which revealed a phylogenetic incongruence between the fish hosts and their parasite fauna. The present study further indicated that the sympatric association between the clariid hosts and non-clariid fishes in Lake Victoria makes it possible for the parasites to switch from one host to another and hence the large number of shared parasites observed. The specificity of some of the parasites, e.g. Diplostomum mashonense and Tylodelphys species 1 & 2 observed is most likely a result of a strong hosthabitat association, such that the position of infective stages (cercariae) in the water column might preclude infection of diplostomids to other clariids. However, this ecological factor, together with the possibility of immuno-physiological barrier requires further investigation.